Parent and Child Media Exposure, Preschooler Dietary Intake, and Preschooler Healthy‐Meal Schemas in the Context of Food Insecurity. (23rd April 2015) - Harrison, Kristen; Peralta, Mericarmen; STRONG Kids Team
<x xml:space="preserve">Abstract</x> Media exposure is correlated with child obesity, yet the family behaviors underlying this link remain poorly understood. Using data from a sample of U.S. parents and their preschoolers, this study assessed parent and child exposure to 5 different media along with child dietary intake. Child healthy‐meal schemas were measured with the Placemat Protocol, a novel play‐based pretend meal assembly activity. Child and parent commercial TV viewing predicted greater obesogenic dietary intake for children in food‐secure but not food‐insecure households. Child commercial TV viewing also predicted a greater proportion of energy‐dense to total foods in children's pretend healthy meals. Discussion focuses on food insecurity as a potential moderator of marketing effects and calls for continued research on child meal schema development.